Influence of the support material on the activity and selectivity of Ru-Sn-B catalysts for the selective hydrogenation of methyl oleate - Sánchez, María Amparo (2015)
The influence of the kind of support (Al2O3, SiO2, and TiO2) on the catalytic activity and selectivity of Ru−Sn−Bcatalysts for the hydrogenation of methyl oleate to oleyl alcohol was studied. The results show that the most active and selectivecatalyst for producing oleyl alcohol is Ru(1%)−Sn(2%)−B/Al2O3. This was attributed to the catalyst having a favorable surfaceSn/Ru ratio (∼2). The SiO2-supported Ru−Sn−B catalyst had a good activity and hydrogenated both C═C double bonds andthe C═O group, thus producing stearyl alcohol with a high yield. It however deactivated, to a great extent, its final conversionbeing lower than that of the bimetallic catalysts supported on Al2O3 and TiO2. The TiO2-supported catalyst had a high selectivityto saturated methyl esters because it hydrogenated C═C double bonds but had little activity for hydrogenation of the C═Ogroup